ChemInform Abstract: Crystal Growth, Structure, Polarization, and Magnetic Properties of Cesium Vanadate, Cs2V3O8: A Structure—Property Study. Issue 29 (1st July 2013) - Yeon, Jeongho; Sefat, Athena S.; Tran, T. Thao; Halasyamani, P. Shiv; zur Loye, Hans‐Conrad
Abstract Single crystals of Cs2V3O8 are synthesized via a two‐step hydrothermal route starting with an aqueous solution of V2O5 and oxalic acid (autoclave, 150 °C, 12 h) followed by addition of Cs2CO3 (150 °C, 24 h; 91% yield).